2021
DOI: 10.3390/reactions3010004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Monoethylene Glycol to Glycolic Acid with Gold-Based Catalyst and Glycolic Acid Isolation by Electrodialysis

Abstract: In this work, a highly selective and active gold-based catalyst for the oxidation of high concentrated monoethylene glycol (MEG) in aqueous solution (3 M, 20 wt%) is described. High glycolic acid (GA) selectivity was achieved under mild reaction conditions. The optimization of the catalyst composition and of the reaction conditions for the oxidation of MEG in semi-batch mode under alkaline conditions led to a GA yield of >80% with a GA selectivity of about 90% in short reaction time. The bimetallic catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…17 Currently, various bimetallic and multimetallic catalysts have been widely used, such as Au-Pt, Au-Pd and Pt-Fe catalysts, which exhibit synergistic effects in accelerating oxidation rates and are more active and selective than single metal catalysts, while also being less prone to deactivation. 18 Shi et al 19 investigated the application of highly active and selective Pt-Fe alloy catalysts prepared on CeO 2 supports in the water-phase oxidation of EG to produce glycolic acid. The results showed that Pt-Fe nanoparticles exhibited a highly alloyed state with a face-centered cubic crystal structure and PtO/FeO chemical states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Currently, various bimetallic and multimetallic catalysts have been widely used, such as Au-Pt, Au-Pd and Pt-Fe catalysts, which exhibit synergistic effects in accelerating oxidation rates and are more active and selective than single metal catalysts, while also being less prone to deactivation. 18 Shi et al 19 investigated the application of highly active and selective Pt-Fe alloy catalysts prepared on CeO 2 supports in the water-phase oxidation of EG to produce glycolic acid. The results showed that Pt-Fe nanoparticles exhibited a highly alloyed state with a face-centered cubic crystal structure and PtO/FeO chemical states.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the deprotonation of H 2 O cannot easily provide OH* 17 . Currently, various bimetallic and multimetallic catalysts have been widely used, such as Au–Pt, Au–Pd and Pt–Fe catalysts, which exhibit synergistic effects in accelerating oxidation rates and are more active and selective than single metal catalysts, while also being less prone to deactivation 18 …”
Section: Introductionmentioning
confidence: 99%